Faktor Pendukung Implemetasi SIMDA dan Pengaruhnya Terhadap Kualitas Laporan Keuangan pada SKPD Kabupaten Kulon Progo - Mohammad Alfian (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
This study determines the factors supporting the implementation of SIMDA (local government’s financial management information system) on SKPDs (local government agencies) and the effect of SIMDA implementation toward financial statement quality. This research was based on the deficient SIMDA implementation, as demonstrated by inadequate accounting information quality. Inadequacy of accounting information quality was indicated by smaller number of SKPDs which obtain an unqualified opinion on their audit report. The population in this research is SKPDs in Kulon Progo, Yogyakarta. The samples were taken using judgmental purposive sampling method. The hypotheses were analyzed using structural equation model through SmartPLS. The results show that the quality of data input and the level of user knowledge about SIMDA positively affects the SIMDA implementation. Moreover, the top management support was not positively influence the SIMDA implementation. Furthermore, the research also found that the SIMDA implementation has positive influence toward the accounting information quality.